7-(3x+3)=5(x-2)

Simple and best practice solution for 7-(3x+3)=5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(3x+3)=5(x-2) equation:


Simplifying
7 + -1(3x + 3) = 5(x + -2)

Reorder the terms:
7 + -1(3 + 3x) = 5(x + -2)
7 + (3 * -1 + 3x * -1) = 5(x + -2)
7 + (-3 + -3x) = 5(x + -2)

Combine like terms: 7 + -3 = 4
4 + -3x = 5(x + -2)

Reorder the terms:
4 + -3x = 5(-2 + x)
4 + -3x = (-2 * 5 + x * 5)
4 + -3x = (-10 + 5x)

Solving
4 + -3x = -10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
4 + -3x + -5x = -10 + 5x + -5x

Combine like terms: -3x + -5x = -8x
4 + -8x = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
4 + -8x = -10 + 0
4 + -8x = -10

Add '-4' to each side of the equation.
4 + -4 + -8x = -10 + -4

Combine like terms: 4 + -4 = 0
0 + -8x = -10 + -4
-8x = -10 + -4

Combine like terms: -10 + -4 = -14
-8x = -14

Divide each side by '-8'.
x = 1.75

Simplifying
x = 1.75

See similar equations:

| 6+5x+5x=66 | | 5x-150=-25 | | 2/3x-10=-2 | | v-2.7=5.58 | | 33=5x+5x+3 | | (m+4n)+(2m-3n)i=13+7i | | -1.8=2 | | 4/6y-8=-4 | | 3x+20=-50 | | 5x+1+6x=111 | | 8(w-7)(-4w-4)=3w | | (K+n)+m= | | 10-(2n-1)=9-3n | | X^2-2.33x-1=0 | | 5a-23=112 | | 9-(4x-4)=8-5x | | 14x-72=180 | | 2(y+7)=17 | | -29d+2d^2=15 | | 8=8v-8v | | 18u+5v^2-35=0 | | h^2+22h+121=0 | | 4w^2+16=0 | | 5x+6x-80=60-9x | | 342x=1026 | | 3x-2=9x+4 | | 4y-48= | | 41y^2=33y | | 18u+5u^2=35 | | 3x+1=4+3x-3 | | -121=-4y^2 | | w+5+2(w+2)= |

Equations solver categories